2011
DOI: 10.2151/sola.2011-022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pollutant Transport on the Air Quality of Shanghai in 2007

Abstract: Pollutant transport has a significant impact on the air quality of Shanghai. To quantify this impact, we comprehensively analyze the characteristics and formation mechanisms of air pollution in Shanghai, using a data set covering five selected air quality monitoring sites and a meteorological site. We find air pollution events occur ~10% of the year. These events are classified into three typical categories, namely the local pollution case (LP), the dust storm case (DS) and the regional transport case (RT), ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Cheng et al (2014) reported that the open biomass burning in the adjacent provinces had significantly affected the air quality in Shanghai. Yan et al (2011) reported that the mean transport contribution to the PM 10 abundance in Shanghai reached 49% during a haze event, and this was almost the same as the contribution from the local emissions. During the world exposition 2010 with strictly controlling local emissions in Shanghai Huang et al, 2013;Zhang et al, 2013), Zhang et al (2013) revealed that transports of regional pollutants affecting air quality in Shanghai mainly originated from the surrounding areas.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Cheng et al (2014) reported that the open biomass burning in the adjacent provinces had significantly affected the air quality in Shanghai. Yan et al (2011) reported that the mean transport contribution to the PM 10 abundance in Shanghai reached 49% during a haze event, and this was almost the same as the contribution from the local emissions. During the world exposition 2010 with strictly controlling local emissions in Shanghai Huang et al, 2013;Zhang et al, 2013), Zhang et al (2013) revealed that transports of regional pollutants affecting air quality in Shanghai mainly originated from the surrounding areas.…”
Section: Introductionmentioning
confidence: 88%
“…Li et al (2012) reported that under the winter monsoon, the northerly air flows from Hebei, Shandong, Anhui, and Jiangsu provinces carried highconcentration PM 10 to Shanghai. Air pollutants can travel through the short transport paths and significantly affect the air quality of the downwind areas (Yan et al, 2011;Li et al, 2012;Yu et al, 2012a, b;Yu et al, 2014a, b).…”
Section: Backward Trajectory and Cluster Analysismentioning
confidence: 99%
“…In recent years the Sahara and western China are recognized as the strongest sources of SDSs globally (Goudie, 2009). SDS also serves as conveyance media of natural minerals and anthropogenic pollutants (Liu et al, 2006;Yan et al, 2011;Kim et al, 2012), potentially inducing climate change (Miller and Tegen, 1998;Zhuang et al, 2001;Qian et al, 2002) and deteriorating ecosystems (Shinn et al, 2000;Garrison et al, 2003;Tan and Shi, 2012). Dust loadings may affect the global environment in many ways by changing, for example, atmospheric radiation balance (Slingo et al, 2006;, cloud formation (Toon, 2003;, convection activity (Stephens et al, 2004;Gong et al, 2010), atmospheric carbon monoxide and sulphur dioxide levels (Adams et al, 2005;Bhattacharjee et al, 2007), biogeochemical cycles (Zhang et al, 2010), and tropical cyclone activity (Evan et al, 2006;Sun et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…NO x , CO and VOCs), which originate mainly from anthropogenic sources (Chameides et al, 1992;Bowman and Seinfeld, 1994;Finlayson-Pitts and Pitts, 1997;Tang et al, 2010). This is true in cities, especially in megacities (Wang et al, 2000;Molina and Molina, 2004;Shao et al, 2006;Chan and Yao, 2008;Ran et al, 2009;Yan et al, 2011). However, frequent high-O 3 events occur not only in cities but also in rural or remote areas, where local emission of anthropogenic pollutants is not important.…”
Section: Introductionmentioning
confidence: 99%